1, 4‐Dioxane‐contaminated groundwater remediation in the anode chamber of a microbial fuel cell. (19th June 2019) - Aryal, Ramesh; Xia, Chunjie; Liu, Jia
Abstract: A two‐chambered microbial fuel cell (MFC) was used for the first time for the remediation of an emerging contaminant—1, 4‐dioxane in its anode chamber. Groundwater historically detected 1, 4‐dioxane contamination was sampled from a Superfund site. Comparative study was carried out between metabolic (i.e., 1, 4‐dioxane as sole carbon source) and cometabolic (i.e., 1, 4‐dioxane and methanol as carbon sources) anodic degradations. It was found that cometabolic degradation increased 1, 4‐dioxane removal by 10%–52% after 7 days and increased maximum power production of the MFC by 18% to 88.9 mW/m 3 . Oxalic acid was detected as a main metabolic degradation product. Beside oxalic acid, acetic acid and isopropanol were also detected as main products for cometabolic degradation. The presence of a biofilm for 1, 4‐dioxane anodic degradation was observed by a scanning electron microscopy. Phyla of Bacteroidetes, Firmicutes, and Proteobacteria, as well as a variety of species, were identified for the first time—especially Rikenella sp. and Solitalea canadensis, whose relative abundances were the highest of 18.8% and 24.0% for metabolic and cometabolic degradation, respectively. This study provided an innovative and sustainable approach for 1, 4‐dioxane anodic biodegradation, which would be potentially utilized for remediation of groundwater contaminated by 1, 4‐dioxane. Practitioner points: Groundwater contaminated with 1, 4‐dioxane was remediated in the anode chamber of a two‐chambered microbial fuel cell. Cometabolic pathway increased 1, 4‐dioxane removal and power production of the MFC compared to metabolic pathway. The presence of a biofilm for 1, 4‐dioxane anodic degradation was observed, and oxalic acid was a main degradation product. This study would be potentially utilized for 1, 4‐dioxane‐contaminated groundwater remediation with simultaneous energy production. External voltage supply for bioelectrochemical remediation of groundwater would potentially be reduced when treating chlorinated hydrocarbons co‐occurred with 1, 4‐dioxane. Abstract : Power production from 1, 4‐dioxane anodic treatment in a microbial fuel cell.